Improving The E-Satisfaction and E-Loyalty Based on E-Trust and E-Service Quality on Shopee Customer - Dila Ayu Ramanda Kuska; Heri Wijayanto; Adi Santoso (Journal of Consumer Sciences, 2024)
The lack of consumer disloyalty in the shopping process, especially amid Shopee's dominance as a market leader, is the focal point of this research. Shopee managed to achieve top rankings in shaping customer loyalty in the online marketplace. This study aimed to identify several factors that affect customer loyalty on the Shopee platform through trust, good service at Shopee, and satisfaction. Considers related to the important role e-satisfaction plays as a mediating variable in understanding the impact of e-trust and e-service quality on Shopee customer loyalty. A quantitative research design was used, with 100 respondents receiving a questionnaire via Google Form, using simple random sampling techniques in data collection. Data analysis was performed through Structural Equation Modeling (SEM) using the SMART PLS application. Research findings show that the impact of e-trust on Shopee consumer loyalty is quite significant and that the quality of e-service also significantly impacts Shopee customer e-loyalty. In contrast, e-satisfaction is a mediator that significantly affects customers’ e-loyalty levels. Managers must focus on improving the quality of e-services for customer satisfaction. This can include continuous measurement and improvement in website consistency, response speed, and information availability.